Latitudinal-dependent emergence of phytoplankton seasonal blooms in the Kuroshio Extension - Sun, Xiying; Chen, Zhaohui; Zhang, Chao; Meng, Siyu (Frontiers in Marine Science, 2023)
The bimodal and unimodal seasonal cycles of surface Chlorophyll-a (Chl-a) concentration (SCC) are ubiquitous in the mid-latitude oceans, having important effects on primary production and carbon transport, with the nutrient and light regarded as two key factors affecting such seasonal difference. However, our quantitative knowledge of distinguishing these two factors is still inadequate in mid-latitude regions where the nutrient and light limit primary productivity simultaneously, hindering the full understanding of the underlying mechanisms of seasonal blooms, as well as the transitions between the bimodal and unimodal seasonal patterns. In this study, the bimodal and unimodal variations of SCC in the Kuroshio Extension (KE) region have been investigated, with a special focus on the emergence latitudes of the secondary peak, i.e., the phytoplankton fall bloom. Based on satellite observations, we have found that the SCC bloom emerges in spring and fall in the northern region, and that spring (fall) bloom starts earlier (later) as the latitude gets higher. In the southern part of KE, by contrast, the SCC tends to peak in late winter or early spring with its bloom time delaying gradually with increasing latitude. A regression model regarding the role of the nutrient and light has been proposed to reconstruct the seasonal variations of the observed SCC, and the relative contributions of the two factors have been assessed quantitatively. It is shown that the regression model has reasonably captured the seasonal variations of SCC in terms of the bimodal/unimodal feature as well as the time of occurrence. Specifically, we have found the boundary between bimodality and unimodality areas moves northward as KE flows eastward, which corresponds to the equivalent contribution of the nutrient and light to the SCC variation and the eastward-decreasing nutrient at the same latitude. Moreover, we have used the model to explore the lag effect of light on regulating the seasonal cycle of SCC, which is associated with the light-heating process, the resultant ocean vertical stratification and the nutrient deficiency. In the context of global warming, our study has provided insights into the switch pattern between bimodality and unimodality of SCC in mid-latitude oceans.